How do you solve 9(2x1)+x=3(6x3)?

1 Answer
Jan 19, 2016

PEMDAS. x=0

Explanation:

To solve this, you have to simplify the equation using PEMDAS; Parenthesis, Exponent, Multiplication, Division, Addition and Subtraction.

First, simplify what's inside the parenthesis. But this does not apply to given equation. There's also no exponent involved so let's just move to multiplication,

9(2x1)+x=3(6x3)
(18x9)+x=(18x9) or (18x9+x=18x9

combine common terms,
19x9=18x9

Then, isolate x by transposing it and combine common terms to solve it,
19x18x=9+9
x=0

checking the solution:
x=0

9(2x1)+x=3(6x3)
9(2(0)1)+(0)=3(6(0)3)
9(1)=3(3)
9=9